Comparison of Two Measures of Working Memory Impairments in 220 Adolescents and Adults With ADHD. Issue 14 (December 2019) - Kennedy, Ryan J.; Quinlan, Donald M.; Brown, Thomas E.
Objective: This study tests the hypotheses that (a) adolescents and adults with ADHD score lower on two normed measures of verbal working memory, relative to their overall verbal abilities, than the general population and (b) a specific story memory test is a more sensitive and relevant measure of working memory impairment than a numerically based test.Method: Scores on normed story memory and numerical memory tests of 220 adolescents and adults with ADHD were corrected for the individual's verbal abilities and compared with each other and national norms.Results: Participants with ADHD scored significantly below their verbal ability measure on both verbal and numerically based memory tests in comparison with national norms. Scores on verbal memory test were lower than scores for numerically based memory tests.Conclusion: This story memory test is a more sensitive measure of working memory impairments in adolescents and adults with ADHD than measures based on recall of numerical data.